Peran Orang Tua untuk Mengurangi Dampak Gawai pada Siswa Sekolah Dasar - Lengsi Manurung; Sigit Widiyarto; Nana Suyana; Iramdan Iramdan (Jurnal Ilmiah Wahana Pendidikan, 2020)
The purpose of this study was to determine the role of parents in home education, second, to describe how parents control the use of devices at home, and third, to describe the extent to which the role of parents in controlling the use of devices in children at home. This research method uses an approach approach. qualitative method is used to examine the condition of an object that is natural, the researcher is the key instrument, data collection is done by triangulation (observation, interviews, documentation). The results showed that there are still some parents who can regulate and control the use of gadgets for children at home. This is due to limited time, not living with parents, and child care has been given to other families or helpers. The impact of excessive use of gadgets needs to be addressed wisely by parents and teachers in schools. Appropriate policies need to be taken. Parents who can already limit the use of devices at home must apply consistently and continuously. Teachers must be able to communicate with parents, so that devices do not damage the system and student achievement.